Comparison of Dynamic Hip Screw and Proximal Femoral Nail in Intertrochanteric Femur Fractures. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the radiological and functional outcome of stable intertrochanteric femur fractures treated with Dynamic Hip Screw(DHS) and Proximal Femoral Nail(PFN).Methods: This randomized controlled trial was conducted in Department of Orthopaedics Pakistan Railway General Hospital Rawalpindi from 20th March 2018 and 19th March 2020. All patients with stable intertrochanteric fractures fulfilling the inclusion criteria were randomly allocated to group A(DHS) and B(PFN). Patients were reviewed radiologically for healing and functional assessment was done with Harris Hip Score(HHS) and graded as poor(score 0.05).Conclusion: For stable intertrochanteric fractures both DHS and PFN yielded similar outcome in terms of radiological union. The short term functional outcome of both DHS and PFN at 3rd and 6th was poor and good but DHS had statistically better score than PFN.At one year follow up both DHS and PFN had similar excellent functional outcome but without any statistically significant difference in the score.